Cross-sectional analysis of risk factors associated with Mugil cephalus in retail fish markets concerning methicillin-resistant Staphylococcus aureus and Aeromonas hydrophila - Attia, Amira S. A.; Abou Elez, Rasha M. M.; El-Gazzar, Nashwa; Elnahriry, Shimaa S.; Alfifi, Ahmed; Al-Harthi, Helal F.; Alkhalifah, Dalal Hussien M.; Hozzein, Wael N.; Diab, Hassan Mohmoud; Ibrahim, Doaa (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction: Aeromonas hydrophila and methicillin resistant Staphylococcus aureus (MRSA) are potent bacterial pathogens possessing major hazards to human health via consuming fish harboring theses pathogens or by cross-contamination beyond the contaminated environment. This study was to determine risk variables associated with the presence of certain pathogenic bacteria from Mugil cephalus fish in retailed market in Egypt. The virulence genes of A. hydrophila and S. aureus was also studied. Furthermore, the antibiotic sensitivity test and multidrug resistance microorganisms were evaluated.In a cross-sectional investigation, 370 samples were collected from mullet skin and muscle samples, washing water, fish handlers, knives and chopping boards. Furthermore, fish handlers' public health implications were assessed via their response to descriptive questionnaire.Results: S. aureus and Aeromonas species dominated the investigated samples with percentages of 26.76 and 30.81%, respectively. Furthermore, A. hydrophila and MRSA were the predominant recovered bacterial pathogens among washing water and knives (53.85 and 46.66%, respectively). The virulence markers; aerA and hlyA were found in 90.7 and 46.5%, of A. hydrophila isolates respectively. Moreover, the virulence, nuc and mec genes were prevailed 80 and 60% among S. aureus isolates, respectively. Antimicrobial susceptibility results revealed that all A. hydrophila isolates were resistant to amoxicillin and all MRSA isolates were resistant to amoxicillin and ampicillin. Remarkably, MDR patterns were highly perceived in A. hydrophila (88.37%) and MRSA (100%) isolates. The prevalence of Aeromonas spp. and S. aureus had positive significant correlation with the frequency of hand washing and using sanitizer in cleaning of instrument. MRSA showed the highest significant prevalence rate in the oldest age category.The pathogenic bacteria recovered in this study were virulent and had a significant correlation with risk factors associated with improper fish handling, as well as the high frequency of MDR detected in these pathogenic bacteria, posing a significant risk to food safety and public health.